Characterization of Two Endo-β-1, 4-Xylanases from Myceliophthora thermophila and Their Saccharification Efficiencies, Synergistic with Commercial Cellulase - Basit, Abdul; Liu, Junquan; Miao, Ting; Zheng, Fengzhen; Rahim, Kashif; Lou, Huiqiang; Jiang, Wei (Frontiers in Microbiology, 2018)
The xylanases with high specific activity and resistance to harsh conditions are of high practical value for biomass utilization. In the present study, two new GH11 xylanase genes, MYCTH_56237 and MYCTH_49824, have been cloned from thermophilic fungus Myceliophthora thermophila and expressed in Pichia pastoris. The specific activities of purified xylanases reach approximately 1,533.7 and 1,412.5U/mg, respectively. Based on multiple template-based homology modeling, the structures of their catalytic domains are predicted. Enzyme activity was more effective in 7.5 L fermentor, yielding 2,010.4 and 2,004.2 U/mL, respectively. Both enzymes exhibit optimal activity at 60°C with pH of 6.0 and 7.0, respectively. Their activities are not affected by EDTA and an array of metal ions. The kinetic constants have been determined for MYCTH_56237 (Km = 8.80 mg/mL, Vmax = 2380 U/mg) and MYCTH_49824 (Km = 5.67 mg/mL, Vmax = 1750 U/mg). More importantly, both xylanases significantly cooperate with the commercial cellulase Celluclast 1.5L in terms of the saccharification efficiency. All these biochemical properties of the xylanases offer practical potential for future applications.